Leveraging a sanitation value chain framework could address implementation challenges and reinvent China’s Toilet Revolution in rural areas - Li, Tianxin; Li, Yufei; Li, Yong; Li, Zifu; Zhou, Xiaoqin; Simha, Prithvi (Frontiers in Environmental Science, 2024)
We evaluated the operational, financial, and management challenges within China's Toilet Revolution by surveying 656 rural households across 10 provinces. The results revealed that the majority of households which renovated their toilets under the Toilet Revolution perceived positive impacts of this on their quality of life and living conditions. Households that had undertaken toilet renovations viewed the program more favorably than households which had not undertaken renovation, and were more willing to engage with the program. Despite the perceived benefits, households were generally hesitant to personally invest in toilet renovation.We uncovered a gap in strategic sanitation planning for post-construction operation and maintenance of toilets, reflecting a "build first, manage later" approach in the Toilet Revolution.We also identified a widespread lack of formal models for management of toilets and toilet products, coupled with high reliance among households on government support and subsidies to fund renovation. To address operational inefficiencies and financial sustainability issues in the program, we propose a novel "Toilet Business" model that leverages a sanitation value chain approach. In this model, private sector engagement, cost management, and market revitalization are crucial components that must be implemented to ensure the program's long-term success.Overall, our study provides valuable insights into the complexities of implementing large-scale sanitation programs such as the Toilet Revolution.